Editorial: Physiological, molecular and genetic mechanisms of abiotic stress tolerance in tropical crops - Chen, Zhijian; Arango, Jacobo; Rao, Idupulapati M.; Liang, Cuiyue (Frontiers Media, 2023)
The tropics are either the center of origin or domestication of many of the economically important crops currently cultivated in the world (Phalan et al., 2013; Fern and Fern, 2014; Laurance et al., 2014). Abiotic stresses, such as drought, chilling, and nutrient deficiency, are the major constraints for plant growth and productivity (Zhu, 2016). Therefore, an improved understanding of the physiological, biochemical, and molecular responses and tolerance mechanisms, along with the discovery of novel stress-responsive pathways and genes, may contribute to efficient breeding strategies that could improve abiotic stress tolerance in tropical crops.